Optimalisasi Realisasi Anggaran Negara/Daerah bagi Pertumbuhan Ekonomi Nasional: Optimizing State/Regional Budget Realization for National Economic Growth - Subekan, Achmat; Azwar, Azwar (LITERA: Jurnal Ilmiah Mutidisiplin, 2024)
This study aims to identify effective efforts in budget realization to optimize its impact on economic growth. The research employs a qualitative approach based on collected data. The analysis technique involves library research using references from books and related scientific articles. Data were obtained from government institutions connected to national/regional budgets and the national economy. The findings indicate that the government must maximize the implementation of national/regional budgets to achieve the highest impact on national economic growth. The first step is ensuring the effectiveness and efficiency of budget expenditure activities, avoiding unnecessary spending and waste. Second, the government should accelerate the realization of national/regional budget expenditures while maintaining attention to national/regional revenue levels. Earlier completion of budget-related activities will provide earlier benefits to society, resulting in a more significant economic growth effect. Third, the integration between national and regional budget realization must be carefully managed to achieve national effectiveness and efficiency. It is crucial to avoid situations where efficiency at the central government level is accompanied by carelessness and waste at the regional level, or vice versa.